Embodying the Interface: Digital Ecologies of Emotion and Knowing - Anabela da Conceição Pereira (PRE-EVENT V ISA FORUM OF SOCIOLOGY Knowing Justice in the Anthropocene, 1-3 July 2025 RC54 & WG08, International Sociological Association, 2025)
Embodied cognition research shows how emotional responses influence attention, memory, cognitive flexibility, and decision-making, particularly in virtual learning environments. Digital contexts reshape bodily and social cues that are essential for constructing meaning, producing distinct cognitive effects based on users’ emotional engagement with the environment. These dynamics raise urgent questions about justice and equity in education: How does the interface include or exclude bodies? How are emotions expressed or suppressed in overstimulated digital spaces? This presentation explores the intersection of digital experience, emotional ecology, and sociotechnical embodiment, examining how platforms like Zoom function as affective ecologies that shape cognition and interaction through embodied emotional responses. Drawing on cognitive science and sociological theory, this research frames the digital interface as both a medium of knowledge and a site of emotional tension and fatigue. Embodiments are presented as a dynamic, emotionally situated, and environmentally embedded process, calling for learning environments that attend to the sensorial, affective, and ecological dimensions of experience. Using Multiple Correspondence Analysis (MCA) and Cluster Analysis from a sample of 300 university students, the study identifies digital fatigue, informational overload, and the perception of technology as an obstacle to social interactions as key variables shaping students’ digital learning experiences. Four user profiles emerged from the analysis: Digital Fluents, Moderate Users, Digital Exhausted Users, and Lost Navigators, reflecting different levels of digital literacy, autonomy, and emotional strain. Responding to the conference theme, this study repositions digital environments within the broader ecology of embodied emotional human experience. The digital is no longer separate from nature – it is part of our emotional and cognitive load. Digital ecologies necessitate recognizing emotion and embodiment as central to learning, inclusion, and sociocultural transformation, thereby promoting digital justice and equity in learning environments.